Desain Implementasi Maximum Power Point Tracking Berbasis Perturb and Observe untuk Optimasi Daya Panel Surya - Evi Nafiatus Sholikhah (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
The purpose of this study is to design the implementation of maximum power point tracking (MPPT) technique based on perturb and observe (P&O) algorithm. The solar panel system is designed from one solar panel connected to a dc-dc buck-boost converter and resistor. The P&O algorithm is implemented as a duty cycle control of the dc-dc buck-boost converter to regulate and track the maximum power point of the solar panel. The system was tested under three different irradiation conditions including 1000 W/m2, 700 W/m2, and 500 W/m2. The test results show that the P&O algorithm successfully tracks and maintains power in the maximum power point (MPP) area with an accuracy of 98% but there are still oscillations in the MPP area due to the ongoing algorithm process.